2021
DOI: 10.1177/00368504211054256
|View full text |Cite
|
Sign up to set email alerts
|

Study on the university students' satisfaction of the wisdom tree massive open online course platform based on parameter optimization intelligent algorithm

Abstract: Introduction: Curriculum learning through the wisdom tree massive open online course platform not only gets rid of the limitations of specialty, school and region, eliminates the limitations of time and space in traditional teaching, but also effectively solves the problem of educational equity. Objectives: This paper proposes an intelligent algorithm combining decision tree, support vector machine, and simulated annealing to obtain the best classification accuracy and decision rules for university students' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…At present, more and more high university teaching management platforms begin to try to adopt big data technology and establish the teaching management platform, but most universities' teaching management platforms are relatively independent and lack communication, and there are many "information silos," which restrict the integration and sharing of educational data [11,12]. erefore, colleges and universities need to build a scientific online education resource exchange and sharing mechanism through mutual communication to promote the intermingling of big data and build a data integration platform.…”
Section: Teaching Management Platformmentioning
confidence: 99%
“…At present, more and more high university teaching management platforms begin to try to adopt big data technology and establish the teaching management platform, but most universities' teaching management platforms are relatively independent and lack communication, and there are many "information silos," which restrict the integration and sharing of educational data [11,12]. erefore, colleges and universities need to build a scientific online education resource exchange and sharing mechanism through mutual communication to promote the intermingling of big data and build a data integration platform.…”
Section: Teaching Management Platformmentioning
confidence: 99%
“…It targets different learning objects, carries out different teaching contents, and achieves different teaching goals. SPOC also has the characteristics of a flipped classroom, and the course learning is completed through SPOC English learning [7]. This paper helps teachers to carry out heuristic teaching in the classroom and focus on explaining the key knowledge structure of the course.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al [34] it is pointed out that an accuracy of 97.2% and a sensitivity of 96.5% validate the capacity of the optimal performance of the classifier algorithm. Similarly, Lee et al [33], accuracy, precision and sensitivity values of 87.44%, 52.84% and 50.68%, respectively, were obtained, which will be applied in the prediction of students who graduate on time. As indicated in [35] a high percentage of sensitivity is important because it reflects the ability of the supervised learning model to predict positive classes and a high percentage of accuracy reflects the ability to distinguish only relevant data.…”
Section: Resultsmentioning
confidence: 79%
“…Likewise, it is similar to the study carried out in [32] where it is indicated that the K-nearest neighbor algorithm presents the best prediction results of users in virtual education environments with an accuracy of 91%. Lee et al [33] where the authors point out that an accuracy greater than 90, it is possible to optimally predict the graduation of the students. This statement is supported by [34], in this study the authors state that in supervised learning the precision of the algorithm depends on the accuracy, for this reason it is important that this indicator provides us with optimal values.…”
Section: Resultsmentioning
confidence: 99%